Dampak Kerjasama Bilateral Currency Swap Arrangement Terhadap Penggunaan Dolar Dalam Perekonomian Indonesia dan Korea Selatan - Harahap, Salma Wanda Alifia; Muhammad Yusra; Poppy Irawan (Hubungan Internasional Universitas Andalas, 2025)
This research aims to further analyze Bilateral Currency Swap Arrangement (BCSA) cooperation between Indonesia and South Korea. This cooperation have agreed to extend on March 6 2020 for the same period of 3 years and worth IDR 115 trillion. The BCSA cooperation is expected to enable currency exchange using local currency. This research aims to see the impact of BCSA collaboration on reduce the use of the United States dollar. The research methods is qualitative methodology where the data for the research is obtained from various reading sources such as scientific journals, news, and official government websites. This research analyzes BCSA cooperation in two relevant dedollarization policies conceptions from IMF Working Paper 2010. Fiscal consolidation explain to maintain the state budget deficit and Monetary Policy carried out by the central bank to achieve inflation stability affect both countries in achieving macroeconomic stability. This research discover the BCSA coorperation achieved a trade surplus during the cooperation and increases the stable foreign exchange reserves of both countries diversification. The increase in the use of local currencies also continues as the country's economy continues to improve. The increase in the use of this currency is also based on ongoing investment and exports.